2021
DOI: 10.1093/infdis/jiab025
|View full text |Cite
|
Sign up to set email alerts
|

Lost in Translation: Lack of CD4 Expression due to a Novel Genetic Defect

Abstract: CD4 expression identifies a subset of mature T-cells primarily assisting the germinal center reaction and contributing to CD8 +-T-cell and B-cell activation, functions and longevity. Herein, we present a family in which a novel variant disrupting the translation-initiation-codon of the CD4 gene resulted in complete loss of membrane and plasma soluble-CD4 in peripheral blood, lymph node, bone marrow, skin and ileum of a homozygous proband. This inherited CD4-knock-out disease illustrates the clinical and immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…However, in both cases, immunodeficiencies were only detected when patients were adults, later than most other primary cellular immunodeficiencies. Interestingly, in both cases, it was shown that helper T cell functions could be performed by DN T cells and/or CD8 + T cells (254,255), similarly to what has been described in in natural hosts of SIV (160,161) and in CD4 knock-out models in mice (240,241). The DN T-cell subset was also expanded, similarly to CD4 KO mice.…”
Section: Absolute Cd4+ T-cell Depletionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, in both cases, immunodeficiencies were only detected when patients were adults, later than most other primary cellular immunodeficiencies. Interestingly, in both cases, it was shown that helper T cell functions could be performed by DN T cells and/or CD8 + T cells (254,255), similarly to what has been described in in natural hosts of SIV (160,161) and in CD4 knock-out models in mice (240,241). The DN T-cell subset was also expanded, similarly to CD4 KO mice.…”
Section: Absolute Cd4+ T-cell Depletionsupporting
confidence: 64%
“…Genetic mutations leading to absolute CD4 + T-cell depletion have been reported in two patients, one 22-year-old female with a mutation in the translation initiation codon of the CD4 gene ( 254 ) and a 45-year-old female with a mutation in a splice acceptor site leading to the expression of a CD4 protein lacking its anchoring domain to the cellular membrane ( 255 ). In the first case, neither CD4 expression on cell membrane, nor soluble CD4 were detected, whereas for the second patient, only CD4 expression on cell membrane was abrogated, while soluble CD4 could still be detected in plasma ( 254 , 255 ). The first patient was hospitalized for severe viral respiratory infection which led to the discovery of her primary immunodeficiency.…”
Section: Other Types Of Cd4 + T-cell Depletionmentioning
confidence: 99%
“…CD3E , which encodes the CD3-epsilon polypeptide, is a built-in multifunctional signal tuner in T-cell development ( 24 ). CD4 , which encodes the CD4 membrane glycoprotein, assists the germinal center reaction and contributes to the activation, functions, and longevity of CD8 + T-cells and B-cells ( 25 ). GATA3 , which encodes a protein of the GATA family of transcription factors, is an important regulator of T-cell development and may be a biomarker associated with poor prognosis in distinct subtypes of nodal peripheral T-cell lymphoma ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the C. albicans lipase Lip2 was recently shown to suppress IL-17 responses by γδ T cells indirectly through inhibition of IL-23 production by tissue-resident DCs 23 . Notably, mucosal CD8 + T cells, γδ T cells and type 3 innate lymphoid cells can compensate for IL-17 production when T H 17 cells are absent, as Cd4 −/− mice are not susceptible to OPC in primary or recall models and patients with lossof-expression CD4 mutations or idiopathic CD4 lymphocytopenia who lack CD4 + T cells are resistant to CMC 18,[24][25][26] . Thus, decreased levels of circulating T H 17 cells may not in isolation be a reliable immunological biomarker for risk assessment of human CMC, and the direct evaluation of global mucosal IL-17 responses may be needed to determine the mechanisms of CMC.…”
Section: Introductionmentioning
confidence: 99%